Answer:
Step-by-step explanation:
(-4,0) ; (-7, -14)
![d=\sqrt{(x_{2}-x_{1})^{2}+(y_{2}-y_{1})^{2}}\\\\ =\sqrt{(-7-[-4])^{2}+(-14-0)^{2}}\\\\ =\sqrt{(-7+4)^{2}+(-14)^{2}}\\\\=\sqrt{(-3)^{2}+(-14)^{2}}\\\\=\sqrt{9+196} \\\\=\sqrt{205} \\\\=14.3178](https://tex.z-dn.net/?f=d%3D%5Csqrt%7B%28x_%7B2%7D-x_%7B1%7D%29%5E%7B2%7D%2B%28y_%7B2%7D-y_%7B1%7D%29%5E%7B2%7D%7D%5C%5C%5C%5C%20%3D%5Csqrt%7B%28-7-%5B-4%5D%29%5E%7B2%7D%2B%28-14-0%29%5E%7B2%7D%7D%5C%5C%5C%5C%20%3D%5Csqrt%7B%28-7%2B4%29%5E%7B2%7D%2B%28-14%29%5E%7B2%7D%7D%5C%5C%5C%5C%3D%5Csqrt%7B%28-3%29%5E%7B2%7D%2B%28-14%29%5E%7B2%7D%7D%5C%5C%5C%5C%3D%5Csqrt%7B9%2B196%7D%20%5C%5C%5C%5C%3D%5Csqrt%7B205%7D%20%5C%5C%5C%5C%3D14.3178)
━━━━━━━☆☆━━━━━━━
▹ Answer
<em>3 × 4 = 4 × 3</em>
▹ Step-by-Step Explanation
You can use any expression that shows the commutative property of multiplication. For example, 3 × 4 = 4 × 3
Hope this helps!
- CloutAnswers ❁
Brainliest is greatly appreciated!
━━━━━━━☆☆━━━━━━━
An x axis because to make a graph you need y and x axis
The slope of the line connecting two points (<em>a</em>, <em>b</em>) and (<em>c</em>, <em>d</em>) is
(<em>d</em> - <em>b</em>) / (<em>c</em> - <em>a</em>)
i.e. the change in the <em>y</em>-coordinate divided by the change in the <em>x</em>-coordinate. For a function <em>y</em> = <em>f(x)</em>, this slope is the slope of the secant line connecting the two points (<em>a</em>, <em>f(a)</em> ) and (<em>c</em>, <em>f(c)</em> ), and has a value of
(<em>f(c)</em> - <em>f(a)</em> ) / (<em>c</em> - <em>a</em>)
Here, we have
<em>f(x)</em> = <em>x</em> ²
so that
<em>f</em> (1) = 1² = 1
<em>f</em> (1.01) = 1.01² = 1.0201
Then the slope of the secant line is
(1.0201 - 1) / (1.01 - 1) = 0.0201 / 0.01 = 2.01